Accounting And Analytical Provision of Corporate Sustainability Development Formation - Tatiana VOROPAYEVA; Natalia CHERNYSCHUK; Svetlana DROBYAZKO; Svitlana LAICHUK; Peter BAGO (Communications of International Proceedings, 2021)
There is a link between integrated reporting and the activity of an enterprise, which is explained by the following factors: depending on the features of the object`s activity (trading enterprise), a certain approach to the formation of integrated reporting is formed, because it is first and foremost necessary for management and investors to make management decisions, so activity indicates key metrics for integrated reporting. In turn, the disclosed information through integrated reporting influences further management decisions that determine the future line of businesses, illustrating the existence of feedback. According to the obtained data, the main theoretical formation provisions of accounting and analytical basis regarding conducting trading enterprises activities in the context of the formation of integrated corporate reporting were formed.
Keywords: corporate reporting; management decisions; integrated reporting; key performance indicators; social responsibility.